Efek Mediasi Corporate Social Responsibility terhadap Hubungan Corporate Governance dan Perceived Market Performance - Sutedjo, Neva Permatasari; Nugroho, Paskah Ika (Jurnal Manajemen dan Bisnis Indonesia, 2018)
This research aims to analyze the organizational performance from customer perspective. On the other hand, the mediation effect of corporate social responsibility toward corporate governance and perceived market performance were also identified. Data were taken from 130 respondents using judgmental sampling. Data were analyzed using SEM with software LISREL 8.8. Results show that corporate governance positively influences corporate social responsibility whereas corporate social responsibility positively influences perceived market performance. It is also found that the mediation effect of corporate social responsibility toward the relationship of corporate governance and perceived market performance is positively confirmed.   Keywords : corporate social responsibility, corporate governance, perceived market performance, mediation effect